ANALISIS KEPUASAN KERJA DOSEN (STUDI KASUS PADA UNIVERSITAS PEKALONGAN) - Siti Nurhayati; Kamalina Din Jannah (LPPM Universitas Pekalongan, 2016)
The aims of this research is to measuring the job satisfaction of lecturer in Pekalongan University. Job satisfaction has 4 indicators, there are satisfaction for the job itself; satisfaction for compensations; satisfaction for job environment ; and satisfaction for colleagues cooperation.The research require primary data, and data collection done with the list of questionnaire as an instrument. The population is all of lecturers at Pekalongan University that amounts 136 persons, and the sample take the amount of 80 lecturers that give responding to questionnaire. The analize done with the Importance Performance Analysis (IPA) approach to measure the job satisfaction for lecturer.The result showed that lecturer job satisfaction generally has Tki = 73,90 %, by the highest Tki on the aspect “the job itself” (by the rate of Tki ≥ 80 %). The other resultexhibited that 3 aspects have the lowest satisfy with Tki amount between 60 % s/d 69 %, and it means that management must increasing soon those aspects, there are : “salary in accordance with qualifying and skills; salary in accordance with workload; and communication that fun between leaders and the lecturer”.